Borate melt structure: Temperature‐dependent B–O bond lengths and coordination numbers from high‐energy X‐ray diffraction. Issue 8 (23rd March 2018) - Alderman, Oliver L. G.; Benmore, Chris J.; Lin, Alex; Tamalonis, Anthony; Weber, J. K. Richard
Abstract: Borate melts containing <20 mol% Na2 O have been studied using high‐energy synchrotron X‐ray diffraction. Temperature dependencies of the mean B–O bond lengths are shown to vary strongly with soda content, by comparison to previous measurements on liquid B2 O3 and Na2 B4 O7 . Whereas in liquid B2 O3 linear thermal expansion of the BØ3 units is observed, with coefficient αBO = 3.7(2) × 10 −6 K −1, this expansion is apparently slightly suppressed in melts containing <20 mol% Na2 O, and is dramatically reversed at the diborate composition. These effects are interpreted in terms of changes in the mean B–O coordination number, where the reaction BØ4 − + BØ3 ⇌ BØ3 + BØ2 O − shifts to the right with increasing temperature. The empirical bond‐valence relationship is used to convert measured bond lengths, r BO, to coordination numbers, n BO, including a correction for the expected thermal expansion. This method is more accurate and precise than direct determination of n BO from peak areas in the radial distribution functions. Gradients of Δ n BO /Δ T = −3.4(3) × 10 −4 K −1 close to the diborate composition, and Δ n BO /Δ T = −0.3(1) × 10 −4 K −1 for a 13(3) mol% Na2 O melt are observed, in reasonable agreement with Raman spectroscopic observations and thermodynamic modeling, with some quantitative differences. These observations go toward explaining isothermal viscosity maxima and changes in fragility across the sodium borate system.